Entrepreneurs’ Courage, Psychological Capital, and Life Satisfaction - Bockorny, Kristi; Youssef-Morgan, Carolyn M. (Frontiers in Psychology, 2019)
Entrepreneurship involves numerous risks and uncertainties. Positive psychological resources such as courage, as well as confidence, hope, optimism, and resilience (collectively referred to as psychological capital), can be valuable for entrepreneurs. This study examines that relationship between entrepreneurs’ courage, psychological capital, and life satisfaction. Results show that entrepreneurs’ courage is related to their life satisfaction, even after accounting for various characteristics of the entrepreneur (demographics and human capital) and the venture (venture size and survival). Moreover, psychological capital fully mediates the relationship between courage and life satisfaction. This is the first study to investigate courage empirically in the context of entrepreneurship, and one of a few studies to apply PsyCap in the entrepreneurial context. It is also the first study to jointly examine courage, PsyCap, and life satisfaction. Implications for future research and practice are discussed.